2015
DOI: 10.1021/acs.jpcb.5b07767
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Solvent Modeling of Solvatochromic Probes in Ionic Liquids: Implications of Solvation Shell Structure

Abstract: Calculations of absorption spectra have been performed for three solvatochromic dyes (para-nitroaniline, N,N-diethyl-para-nitroaniline, and Reichardt's dye) in four ionic liquids based on 1-ethyl-3-methylimidazolium cation. Different variants of explicit solvent model have been used: fully explicit representation of solvent ions, charge embedding method, and mixed approach. Electrostatic solute-solvent interactions have been shown to induce structuring of the solvation shell around dipolar solute, causing sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…In view of the surprising agreement of gas-phase quantum chemical results with experimental bulk solvent spectra of EMIM-TFSI , and the apparent failure of the implicit solvent model to improve the description of spectral characteristics, we decided to test the explicit approach in computations of EMIM-TFSI IR and UV–vis spectra. The electronic absorption spectrum will be modeled as in our recent work on solvatochromic dyes in ILs, using a sequential approach of classical or ab initio molecular dynamics (AIMD) simulations followed by TD DFT calculations for selected geometries. Vibrational spectra can be successfully obtained from AIMD trajectories via Fourier transform; in this work, we will apply this methodology to the infrared absorption spectrum of EMIM-TFSI liquid.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the surprising agreement of gas-phase quantum chemical results with experimental bulk solvent spectra of EMIM-TFSI , and the apparent failure of the implicit solvent model to improve the description of spectral characteristics, we decided to test the explicit approach in computations of EMIM-TFSI IR and UV–vis spectra. The electronic absorption spectrum will be modeled as in our recent work on solvatochromic dyes in ILs, using a sequential approach of classical or ab initio molecular dynamics (AIMD) simulations followed by TD DFT calculations for selected geometries. Vibrational spectra can be successfully obtained from AIMD trajectories via Fourier transform; in this work, we will apply this methodology to the infrared absorption spectrum of EMIM-TFSI liquid.…”
Section: Introductionmentioning
confidence: 99%
“…They compared the experimental results with the electronic transition energies obtained from time‐dependent density functional theory (TD‐DFT) calculations (TD‐CAM‐B3LYP/aug‐cc‐pVTZ level of theory) and concluded that the absorption spectra in the investigated region is mostly due to the imidazolium cation. Eilmes and co‐workers reported the comparison of experimental and calculated absorption spectra of solvatochromic dyes ( para ‐nitroaniline, N,N ‐diethyl‐ para ‐nitroaniline, and Reichardt's dye) in four ionic liquids: [C 2 C 1 im][BF 4 ], [C 2 C 1 im][Tf 2 N], [C 2 C 1 im][PF 6 ], and [C 2 C 1 im][FSI] . The authors ran MD simulations (both with classical FF and AIMD for [C 2 C 1 im][Tf 2 N]) and used the trajectory to select clusters composed of the probe dye plus a layer of solvating ILs, considering several solvation protocols.…”
Section: Electronic Spectroscopymentioning
confidence: 99%
“…Today there is a large variety of published solvatochromic dyes corresponding to different media, e.g. organic solvents [8,10], ionic liquids [10,11], solvent mixtures [10,[12][13][14][15] or solvent comprising polarity modifiers [16]. What often appears to be challenging is the choice of a suitable solvatochromic probe for the description of a physicochemical problem encompassing solvent polarity effects.…”
Section: Introductionmentioning
confidence: 99%